Forest city: not easy to acquire citizenship - Kamarudin, Abdul Rani (New Straits Times (Malaysia), 2017)
It is not easy for a foreigner living in Malaysia to acquire Malaysian Citizenship.What ther requisites to qualify for citizenship is briefly discussed.